ANALISIS POTENSI DAN PENGEMBANGAN AGROWISATA SUBAK DI DESA JATILUWIH KECAMATAN PENEBEL KABUPATEN TABANA PROVINSI BALI - I Kadek Ngara Kariadi; Siti Syamsiar; Ni Made Suyastiri (Jurnal Dinamika Sosial Ekonomi, 2017)
The purpose of this study are: (1) to analyze the potential of agro-tourism in the village of Jatiluwih (2) to analyze the development of agro-tourism in the village Jatiluwih Subak (3) to analyze the increase in yhe income of farmers with agro-tourism in the village Jatiluwih Subak. The basic method used in this research is descriptive method. Method of determining the location of the research is purposive. The sampling method used was accidental sampling and proportional random sampling. Methods of analysis using the t test is one sample t-test and T-test dependent. Results of the study are: (1) The potential for agro-tourism in the village Jatiluwih Subak high (2) Development of agro-tourism in the village Jatiluwih Subak high (3) Agro increase the income of farmers in the village of Jatiluwih. Keywords: Potential, Development of Agro-tourism, Income